Comparative molecular characterisation of adipose tissue - Choong, Siew Shean (2016)
Adiposity is linked to reproductive efficiency as adipose tissue (AT) is known to influence the hypothalamic-pituitary-gonadal axis, although the exact roles of AT remain poorly understood. Different cattle and pig breeds exhibit different adiposity and reproductive characteristics. The hypothesis is that differences in adiposity underpin the phenotypic differences in reproductive performance in these animals. To test this hypothesis, next generation RNA sequencing analysis was completed of AT from (i) cattle (Holstein, Hereford and Aberdeen Angus cross breeds enrolled in a dietary protein feed trial), (ii) European Large White and Asian Meishan pigs and (iii) African elephants. Differentially expressed genes (DEG) were determined in each species and validation completed utilising quantitative reverse transcriptase PCR (qRT-PCR). Results revealed significant DEG involved in adipogenesis and lipogenesis between (i) breeds, (ii) resulting from the dietary protein intervention and (iii) sexes and age groups. Fatty acid (FA) composition of AT from different cattle breeds and dietary protein levels was determined using gas chromatography and compared, although significant difference was not observed. Gene networks related to vitamins A and D suggest potential nutritional influences on adipogenesis and lipogenesis, consequently vitamin levels in feed may impact adiposity and thereby animal reproductive performance. Results from the elephants indicated disparity in energy storage and utilisation between sexes and age groups, thus this can provide baseline information to improve captive population management of these animals in different life stages. By exploiting comparative inferences from previous human and animal studies to the results obtained from this study, a positive influence of adiposity on fertility was identified. Future work should verify whether differential mRNA expression of genes of interest identified are reflected in protein expression. Also additional studies into the FA profiles of other biologically relevant tissues are warranted to enable comparison of FA uptake and usage between AT and other tissues.